Speaking with pictures: folk art and the narrative tradition in India - Chatterji, Roma (New Delhi Routledge, 2012)
This book explores visual narratives in folk art, particularly the scroll painting tradition of the patuas of West Bengal and the Pardhan-Gond style of Madhya Pradesh. It foregrounds folk art$1 (Bs engagement with modernity by re-looking at its figurative modes and the ways in which they are embedded in mythic thought.s
Keywords: Folk art India; Art and mythology; Graphic Novel